ANALISIS METODE AKUNTANSI PERSEDIAAN DILIHAT DARI PERTUMBUHAN LABA DAN MARKET VALUE (Studi pada Industri Manufaktur yang Terdaftar di BEI Tahun 2009-2010) - Andy Christian; Supatmi . (Jurnal Bisnis dan Ekonomi, 2013)
There are two methods of accounting for inventories that can be used by companies according to accounting standards and tax regulations in Indonesia, i.e. first-in, first out (FIFO) and average. The use of different inventory accounting methods would result in the difference of the value of ending inventory, cost of goods sold, and net income. This research analyzes whether there is a difference in the earnings growth and market value of companies using the FIFO and average. This research uses data of manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2009-2010 with samples 13 companies using FIFO method and 67 companies using average method. Earnings growth used in this research are the growth in gross profit and net profit. Profit growth is calculated by measuring the change in earnings relative to the profits in the previous period. While the company's market value is measured using market capitalization. Testing the hypothesis in this study using Mann-Whitney U non-parametric significance test. This research found that there is no significant difference in gross profit growth and net profit growth between companies using FIFO and average method method. However, in between the two groups of companies, there is a significant difference in market value. Key words: inventory accounting method, market value, earnings growth